Central obesity and its associated factors among cancer patients at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Molla, Meseret Derbew; Wolde, Haileab Fekadu; Tafesse Teferi, Ephrem; Kibret, Anteneh Ayelign (Frontiers in Oncology, 2023)
Purpose: Obesity, especially the hidden type of obesity (central obesity) has been believed to be the major risk factor for the development and progression of non-communicable diseases, including cancers. However, there is a limited number of studies regarding the issue in Ethiopia and the study area. Therefore, this study aimed to evaluate the magnitude of central obesity and its associated factors among cancer patients visited in the oncology unit of the University of Gondar Comprehensive Specialized Hospital. Methods: an institutional-based cross-sectional study was conducted from January 10 to March 10, 2021. A total of 384 study participants were enrolled using a systematic sampling technique. The data were collected using a semi-structured interviewer-administered questionnaire and were pretested to address the quality of assurance. The weight of the participants was assessed using body mass index (BMI) and central obesity. Both bivariate and multivariate logistic regressions were conducted to identify the factors associated with central obesity, and p-values less than 0.05 with multivariate were considered statistically significant associations. Result: Most of the respondents (60.16%) were stage I cancer patients. The study found that about 19.27% of the participants were prevalent in central obesity, and none of them were obese by body mass index (BMI) categorization criteria. However, about 12.24% and 7.03% of the participants were found to be underweight and overweight, respectively. The variables associated with central obesity were sex (AOR=14.40; 95% CI: 5.26 - 39.50), occupation (AOR=4.32; 95%CI: 1.10 - 17.01), and residency (AOR=0.30; 95% CI: 0.13 - 0.70). Conclusion: a significant number of the respondents (19.27%) were centrally obese. Being female, urban residency and occupation other than farmer, merchant, and governmental were the factors associated with central obesity. Hence, cancer patients may be centrally obese with normal body weight.